Career Panel for Pathology Residents: Going Beyond the Core Curriculum. Issue 4 (1st April 2014) - Guarner, Jeannette; Hill, Charles E.; Caliendo, Angela M.
Abstract: Objectives: To increase awareness in pathology residents of different career choices and familiarize them with the job market. Methods: For 3 years, community pathologists and faculty members participated in half-day panels that residents attended voluntarily. Panelists presented their professional life experiences and shared advice. We showcase the implementation and resident evaluation of these panels. Results: Panelists were rated as outstanding or excellent for relevance. Residents chose the following themes as most useful: visualizing the array of practices (community, part-time, public health, and others), careers that follow unexpected courses and people taking advantage of opportunities as they happen, knowing that not having a definitive direction is frequent, and finding out what different practices look for when they are hiring. Conclusions: Career planning is a neglected aspect of pathology residency training, and panels in which pathologists present their experiences are helpful to prepare residents for what lies ahead.